A review on water demand analyses, provisioning service and cultural service from ecosystem of kenyir lake, terengganu, Malaysia - Azlan N.N.I.M.; Malek M.A.; Salina D.; Salim J.M.; Mohammad T.A. (IAEME Publication, 2023)
This paper presents a synoptic survey on water demand estimation and the literature review on provisioning services and cultural services that is applicable for Kenyir Lake, Terengganu, Malaysia. A good water demand method serve as one of the principal role in planning, operation and management of water supply system of an area. The water demand methods consider geography of the region, weather and community characteristics. Identification of ecosystem services namely provisioning services and cultural services in relation to ecosystem of Kenyir Lake clarify the contribution of those services in economy. This paper concludes that applicable water demand estimation for Kenyir Lake is micro-component analysis method. Meanwhile for the provisioning service is aquaculture and the cultural services are recreation, ecotourism and cultural heritage have been analysed from ecosystem of Kenyir Lake. IAEME Publication.